Keterpakaian Database ProQuest oleh Mahasiswa dalam Penulisan Karya Ilmiah (Studi Kasus: Program Studi Perpustakaan dan Ilmu Informasi) - Miranda, Annisa; Marlini, Marlini (YASIN, 2025)
This study is motivated by the limited research on the utilization of the ProQuest database in higher education environments, despite the critical role of scholarly databases in supporting the quality of students' academic writing. The purpose of this study is to analyze the utilization of the ProQuest database by students in the Library and Information Science Program at Universitas Negeri Padang in their academic writing processes. A descriptive quantitative method with a case study approach was employed, involving 66 students from the 2021 and 2022 cohorts selected through purposive sampling. Data were collected using a questionnaire based on the Technology Acceptance Model (TAM), with two main indicators: Perceived Usefulness and Perceived Ease of Use. The results showed that students’ perceptions of the usefulness of ProQuest were relatively high, with an average score of 3.11, while their perceptions of ease of use were relatively low, with an average score of 2.18. These findings indicate that although students recognize the benefits of ProQuest, barriers remain in terms of accessibility and usability. Therefore, enhancing digital information literacy and providing technical training are essential to optimize the use of ProQuest as a credible reference source in students' academic writing.